The Influence of Religious Education Based Parenting Patterns on the Social Development of Elemetary School Students - Maharani Lintang Corneasari (CV Projurnal Mitra Publikasi, 2025)
This study aims to examine the influence of religious-based parenting on the social development of elementary school students. The research was conducted in Semarang Regency, involving 40 elementary school students, divided into two groups: 20 students attending religious-based schools and 20 students attending national schools. This study uses a quantitative approach with a comparative design to compare the social development of students based on religious-based parenting. Data were collected using a questionnaire that measured aspects of social development, such as the ability to interact with peers, empathy, and the ability to adapt to social situations. The results of the study showed that students from religious-based schools tended to have better social skills, with higher levels of empathy and cooperation compared to students in national schools. This indicates that religious-based parenting can have a positive impact on students' social development, particularly in fostering better social character. The study provides recommendations for educators and parents to consider parenting approaches that support positive social development, both in the family and school environment.